Concurrent hyperthyroidism and papillary thyroid cancer: a fortuitous and ambiguous case report from a resource-poor setting. (December 2016) - Kadia, Benjamin; Dimala, Christian; Bechem, Ndemazie; Aroke, Desmond
Abstract Background Concurrent thyroid cancer (TC) and hyperthyroidism (HT) is rare though increasingly being reported. HT due to TC is much rarer and more challenging especially in Africa where TC and HT have significant case fatality rates. Case presentation We present a 37-year-old Cameroonian female who had been on irregular regimens of propranolol and digoxin as treatment for worsening palpitations for 12 months. She came to our district hospital for her propranolol medication refill. We fortuitously identified features of HT and found a left uninodular goiter with no cervical lymphadenopathy. She was referred for thyroid assessment which suggested primary HT and an enlarged heterogeneous left lobe with a well-defined homogenous solid mass. We restarted her on propranolol and referred her for a course of methimazole. At the referral hospital, she also underwent a left thyroid lobectomy. The resected lobe was sent for histopathology which revealed a neoplastic nodule with features suggestive of a papillary thyroid cancer (PTC) causing HT. The patient's clinical progress postoperatively was good and there was regression of hyperthyroid symptoms. Conclusions The historical, clinical, and laboratory findings were suggestive of HT due to PTC. A high index of suspicion, prompt referral and counter-referral lead to a positive outcome of such a rare case in a resource poor setting. We advocate for systematic and careful evaluation of all thyroid nodules.